Platelet indices as a predictor in patients with aplastic anemia and immune thrombocytopenic purpura: a retrospective case-control study - Mahynour Z. Abdel Hi; Safaa A. A. Khaled; Dalia G Mahran; Mai M. Aly (SpringerOpen, 2024)
Abstract Background and objectives Platelet indices are widely available and relatively cheap platelet parameters. The critical objective of this study is to assess the reliability of platelet indices as biomarkers for diagnosis and prognosis in adult thrombocytopenic patients. Methods A retrospective case-control study, including 81 immune thrombocytopenia (ITP) cases, 50 aplastic anemia (AA) cases, and 150 participants as a control group. This study included patients admitted from 2016 to 2021 to the Clinical Hematology Unit, Department of Internal Medicine, University Hospital. The collected data included sociodemographic information, clinical data, laboratory data, and an assessment of the therapeutic response in the studied groups. Results For the diagnosis of adult thrombocytopenic patients, platelet distribution width (PDW) showed the best diagnostic accuracy (85% for ITP and 91.9% for AA) at cutoff points of 14.9% and 17.2%, respectively. This was followed by mean platelet volume (MPV) with diagnostic accuracies of 77% for ITP and 89.3% for AA at a cutoff point of 9.4 fl. Platelet large cell ratio (PLCR) demonstrated insignificant accuracy in diagnosing either ITP or AA. Conclusion Platelet indices can play a crucial influence in the diagnosis, not the prognosis, of adult thrombocytopenia. Trial registration NCT05116033. https://classic.clinicaltrials.gov/ct2/show/NCT05116033